Respuesta :

Answer:

(y+6)(y-1)

Step-by-step explanation:

literally factorising.

y^2 x -6 = -6y^2

u need two numbers that multiply to make -6 and add them together to make +5 which is +6 and -1.

Answer:

p = 6, q = - 1 , or p = - 1, q = 6

Step-by-step explanation:

Factorise the quadratic expression on the left side

y² + 5y - 6

Consider the factors of the constant term (- 6) which sum to give the coefficient of the y- term (+ 5)

The factors are + 6 and - 1 , since

6 × - 1 = - 6 and 6 - 1 = + 5 , then

y² + 5y - 6

= (y + 6)(y - 1) = (y - 1)(y + 6)

Compare to (y + p)(y + q) , then

p = 6, q = - 1 or p = - 1, q = 6